2012
DOI: 10.1308/003588412x13171221498460
|View full text |Cite
|
Sign up to set email alerts
|

Lesions of uncertain malignant potential (B3) on core biopsy in the NHS Breast Screening Programme: is the screening round relevant?

Abstract: INTRODUCTION Most women who have screening mammography and undergo subsequent open biopsy following an indeterminate core biopsy result are eventually found to have benign disease. However, a significant number have malignant disease and the rate of malignancy in such cases may be influenced by various factors. This study examined the effect of the type of screening round (prevalent or incident) on the likelihood of breast cancer being present. METHODS A total of 199 women who had NHS breast screening mammogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…93 These rates are again consistent with the rate observed among UK NHS breast-screening programme participants, whereby 70% of diagnostic biopsies resulted in benign diagnoses. 94 The proportion of benign diagnoses is even greater when taking into account diagnostic work-ups carried out by means of additional imaging and clinical examination. Data from the BCSC registries demonstrated that of 4082 patients prescribed to diagnostic follow-up by means of imaging, clinical follow-up or biopsy following mammographic screening, only 316 cases were diagnosed as invasive cancer or DCIS.…”
Section: Risk-benefit Analysis Diagnostic Follow-upmentioning
confidence: 99%
“…93 These rates are again consistent with the rate observed among UK NHS breast-screening programme participants, whereby 70% of diagnostic biopsies resulted in benign diagnoses. 94 The proportion of benign diagnoses is even greater when taking into account diagnostic work-ups carried out by means of additional imaging and clinical examination. Data from the BCSC registries demonstrated that of 4082 patients prescribed to diagnostic follow-up by means of imaging, clinical follow-up or biopsy following mammographic screening, only 316 cases were diagnosed as invasive cancer or DCIS.…”
Section: Risk-benefit Analysis Diagnostic Follow-upmentioning
confidence: 99%
“…Most of the studies in the literature discuss the outcome of B3 lesions following a stereotactic biopsy because they usually manifest as microcalcifications or architectural distortions recognized on mammography or digital breast tomosynthesis during breast screening …”
Section: Introductionmentioning
confidence: 99%
“…In the context of public health care, the financial and planning costs might be an obstacle to implement such a short-term follow-up. In the Netherlands, approximately 1 million women join the breast screening program every year, and in Australia and England 1.5 million 27 and 2 million, 28 respectively. Between 1% and 15% of all patients attending breast cancer screening programs worldwide are recalled for further assessment, 29 32 and pure calcifications classified as B3 account for approximately 8% of all patient recalls.…”
Section: Discussionmentioning
confidence: 99%
“…In light of these figures, the Dutch National Breast screening program has abandoned the use of B3 for calcifications; instead, B3 lesions are directly classified as B4 and all of them should undergo further investigation. 28 , 37 , 38 The most recent edition of the BI-RADS suggests avoiding the use of the B3 category in large population screening programs. 10 …”
Section: Discussionmentioning
confidence: 99%